1989
DOI: 10.1159/000205275
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stromal Cells in Myeloproliferative Disorders

Abstract: The number of bone marrow-derived fibroblastoid colony-forming cells (CFU-F) and the production of colony-stimulating activity (CSA) by bone marrow stromal cells were studied in 71 patients with myeloproliferative disorders (MPD). The numbers of CFU-F in chronic-phase chronic myelogenous leukemia (CML), polycythemia vera (PV) and essential thrombocythemia (ET) were not different from those in normal subjects. However, the number of CFU-F in acute-phase CML was markedly decreased. Bone marrow adipocyte colony-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…32 Taken together with our observation of impaired adipogenic differentiation of AA MSC including morphological abnormalities and decreased level of IGF-1 expression, the data hint that adipogenic differentiation is impaired at times that correlate with the worst phases of hematopoietic depression. Fat cells are necessary for the adequate maintenance of hematopoiesis, and their dysfunction in the worst phase of the disease points to the existence of secondary alterations in MSC of AA patients.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…32 Taken together with our observation of impaired adipogenic differentiation of AA MSC including morphological abnormalities and decreased level of IGF-1 expression, the data hint that adipogenic differentiation is impaired at times that correlate with the worst phases of hematopoietic depression. Fat cells are necessary for the adequate maintenance of hematopoiesis, and their dysfunction in the worst phase of the disease points to the existence of secondary alterations in MSC of AA patients.…”
Section: Discussionsupporting
confidence: 61%
“…[26][27][28] The CFU-F concentration in the BM varies among patients with different hematologic diseases, [29][30][31] and it may also depend on the treatment or phase of the disease. 7,32,33 The characteristics of CFU-F could therefore potentially be used for monitoring the function of the stromal microenvironment over the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…3) [22]. This was not explained by changes in the production of any of the known stimulatory or inhibitory cytokines [22,101,173,214,215].…”
Section: Stromal Abnormalities In CMLmentioning
confidence: 99%
“…CML fibroblasts exhibited the same proliferative behavior and protein synthesizing capacity as normal fibroblasts [34]. In the majority of cases reported, the numbers of CFU-F were within the normal range [23,101,114,162,219]. The number of adipocyte colony-forming cells was often increased [101], a finding which is difficult to reconcile with the already mentioned reduction in fat cells in histological sections [130].…”
Section: Stromal Abnormalities In CMLmentioning
confidence: 99%
“…Nevertheless, such patients often later progress to myelofibrosis. Analysis of CFU-F in the bone marrow of the patients with chronic myeloid leukemia and polycythemia vera revealed that the growth characteristics of this precursor were unchanged [16, 17]. Summarizing the data, one could suggest a possible interconnection between the quality of hematopoiesis and the functional status of the stromal microenvironment.…”
Section: Introductionmentioning
confidence: 99%